Half the village - Hooker, R. H. (Islam and Christian-Muslim relations, 1995)
In 1947 India became independent and at the same time lost a large part of its territory to the newly created state of Pakistan. This new political arrangement was achieved at a terrible cost in terms of human life and suffering. The years up to and immediately following 1947 provoked a debate about national and human identity. Pakistan was founded on the grounds that Muslims could not be safe or prosperous under majority Hindu rule in newly independent India. The new India insisted that she was a secular democracy in which all religious communities could enjoy equal status. The debate is reflected in a number of Hindi-language novels which deal with this period. The present article is about one of them, written by a member of India's small Shi'ite Muslim community who was also a Marxist. The debate raises issues about human identity which we can now see as being tragically and importantly relevant for contemporary Europe. These issues are not only political but also religious in that they go to the heart of our understanding of what it means to be human beings. The article points to some of these issues and at the same time argues that the novel as a literary form provides a valuable and significant vehicle for their discussion.